A Methodological Approach to Evaluating the Progress of the Implementation of the Smart City Concept in Ukrainian Cities - Poliakova Olha Yu.; Pozdniakova Anna M. (Problemi Ekonomiki, 2019)
Ukrainian cities are joining the global movement for digitalization. They have gradually started to use benefits of ICT, claiming their smartness and promoting newly implemented technological solutions. However, till the date we do not have a commonly accepted definition or framework for measuring their success. Based on the reviewed international and national frameworks, there proposed a methodological approach to evaluating the progress of Ukrainian cities in implementing the Smart Sustainable City Framework. The research takes into account both the theoretical base (components and definitions of Smart Sustainable City defined by different scholars) and practical side (the available evaluation methodologies). The developed Framework comprises two stages: a) creation of conditions for concept building; b) actual measurement of sustainability and smartness of cities, each of which including several dimensions. The model uses 54 indicators, the data being taken from both official statistical sources and survey data. The methodology has been used to measure the index of six selected Ukrainian cities that are considered quite progressive in terms of ICT usage and smart solution implementation. The results reveal that cities with officially adopted relevant strategies typically demonstrate better results than those that implement innovations on an ad-hoc basis.